2005
DOI: 10.1093/jn/135.3.499
|View full text |Cite
|
Sign up to set email alerts
|

(n-3) Fatty Acids Reduce the Release of Prostaglandin E2 from Bone but Do Not Affect Bone Mass in Obese (fa/fa) and Lean Zucker Rats,

Abstract: Childhood obesity is prevalent and linked to the development of Type 2 diabetes mellitus (DM) and poor bone health. Some PUFA enhance bone mass and thus may improve bone health in obese children. The study objective was to determine the effects of dietary (n-6) compared with (n-3) essential PUFA and long-chain PUFA (LCPUFA) on bone in an obese and insulin-resistant state. Male fa/fa (n = 48) and lean Zucker rats (n = 48) were fed diets containing safflower oil [SO, high (n-6) PUFA], flaxseed oil [FXO, high (n-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 65 publications
7
25
3
Order By: Relevance
“…Enzyme activity was expressed as U/L. Bone organ culture was performed as previously described (Blanaru, Kohut, Fitzpatrick-Wong, & Weiler, 2004;Mollard et al, 2005b;Watkins et al, 2000a;Watkins et al, 2001e). Briefly, tibia samples (1 g) were incubated in 10 ml of Hank's balanced salt solution (Mediatech, Inc., Manassas, VA, USA) for 2 h at 37°C in a shaking water bath, followed by the removal of bone and rapid freezing of solution at À20°C for 1 week until duplicate analysis of PGE 2 by a competitive enzyme-linked immunosorbent assay (ELISA) technique using a rabbit polyclonal antibody PGE 2 kit (Oxford Biomedical Research, Inc., Oxford, MI, USA).…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzyme activity was expressed as U/L. Bone organ culture was performed as previously described (Blanaru, Kohut, Fitzpatrick-Wong, & Weiler, 2004;Mollard et al, 2005b;Watkins et al, 2000a;Watkins et al, 2001e). Briefly, tibia samples (1 g) were incubated in 10 ml of Hank's balanced salt solution (Mediatech, Inc., Manassas, VA, USA) for 2 h at 37°C in a shaking water bath, followed by the removal of bone and rapid freezing of solution at À20°C for 1 week until duplicate analysis of PGE 2 by a competitive enzyme-linked immunosorbent assay (ELISA) technique using a rabbit polyclonal antibody PGE 2 kit (Oxford Biomedical Research, Inc., Oxford, MI, USA).…”
Section: Sample Collectionmentioning
confidence: 99%
“…In addition to the alteration in PGs production, some researchers have indicated that the biological mechanisms involving the role of x3 and x6 polyunsaturated fatty acids in bone metabolism (formation and resorption) include osteoblasts differentiation and proliferation, calcium absorption and excretion, inflammation, and lipid oxidation (Claassen, Coetzer, Steinmann, & Kruger, 1995a;Corwin, 2003;Haag, Magada, Claassen, Bohmer, & Kruger, 2003;Mollard, Gillam, Wood, Taylor, & Weiler, 2005b;Parhami, 2003;Sun et al, 2004;Watkins et al, 2000a;Watkins et al, 2001b;Watkins et al, 2003). Therefore, by including x6 (ARA) and x3 (EPA & DHA) LC PUFA and altering their ratio in the diet, it is possible to influence the amount of PGE 2 in bone thus reach an amount that would favor bone formation versus resorption.…”
Section: Introductionmentioning
confidence: 99%
“…Other developmental models (Weiler et al 2002Mollard et al 2005) that are representative of disease states (polycystic kidney disease, inflammatory bowel disease, hyperinsulinemia) are discussed in Section 21.7.1.4 (Table 21.9).…”
Section: Feeding Intervention Trials In Developing Animal Modelsmentioning
confidence: 99%
“…The effects of FS oil or FS oil in combination with SDG have been investigated using animal models of kidney disease (Weiler et al 2002, obesity (Mollard et al 2005) and inflammatory bowel disease (Table 21.9). Compromised bone health is a secondary characteristic of these diseases.…”
Section: Feeding Intervention Trials In Animal Models Of Disease Statesmentioning
confidence: 99%
See 1 more Smart Citation